“Your Womb is Our Enemy!” - Muauz Gidey Alemu; Mulugeta Gebrehiwot Berhe (Journal of BRICS Studies)
War crimes, crimes against humanity and genocide were committed in the war in Tigray.  This article focuses on the use of sexual violence as an instrument of war. It narrates the scale, nature, and intentions of the sexual violence perpetrated on Tigrayan women, girls, men and boys. It showcases the extreme cruelty, dehumanization and intent to sterilize and inflict maximum damage from stories of victims and witnesses. It compares them with the rape crimes committed in other cases and concludes the nature of the crime was genocidal.